Meta Analisis : Risiko Kredit dan Profitabilitas Bank - Artha, I Wayan Budi; Antari, Ni Luh Sili (Value : Journal of Management and Business, 2026)
Credit risk is one of the main risks faced by banks and has a direct impact on financial performance, particularly bank profitability. Various empirical studies have produced mixed findings regarding the relationship between credit risk and profitability, demonstrating negative, positive, and insignificant effects. Therefore, this study aims to conduct a meta-analysis to systematically integrate and evaluate the results of previous studies on the effect of credit risk on bank profitability and to examine whether there are differences in the effect of credit risk on profitability of banks in Indonesia and banks outside Indonesia. The meta-analysis method was used to calculate the pooled effect size and to examine the level of heterogeneity between studies. The results of the meta-analysis indicate that credit risk has a negative and significant effect on bank profitability. An increase in the non-performing loan ratio tends to reduce bank profits through increased provisioning costs and decreased net interest income. There was also no difference in the effect of credit risk on profitability between banks in Indonesia and banks outside Indonesia. These findings emphasize the importance of effective credit risk management as a key to maintaining stable performance and sustainable bank profitability.